2016
DOI: 10.1021/acscatal.6b01421
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Tetrapyrazolyl Palladium Complexes Exhibiting Facile Tandem Transfer Hydrogenation/Suzuki Coupling Reaction of Fluoroarylketone

Abstract: Herein, we report an example of dinuclear pyrazolyl-based Pd complexes exhibiting facile tandem catalysis for fluoroarylketone: Tetrapyrazolyl di-palladium complexes with varying Pd-Pd distances efficiently catalyze the tandem reaction involving transfer hydrogenation of fluoroarylketone to the corresponding alcohol and Suzuki-Miyaura cross coupling reaction of the resulting fluoroarylalcohol under moderate reaction conditions, to biaryl alcohol. The complex with the shortest Pd-Pd distance exhibits the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 79 publications
1
24
0
1
Order By: Relevance
“…These latter two compounds, similarly to the nitrile derivative, acted as catalyst poisons and prevented the reduction of nitrobenzene to aniline as well. Such preference for the oxidative insertion of Pd into the Ar–halogen bond over the reduction has been recently reported in tandem Suzuki coupling/transfer hydrogenation sequences …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These latter two compounds, similarly to the nitrile derivative, acted as catalyst poisons and prevented the reduction of nitrobenzene to aniline as well. Such preference for the oxidative insertion of Pd into the Ar–halogen bond over the reduction has been recently reported in tandem Suzuki coupling/transfer hydrogenation sequences …”
Section: Resultsmentioning
confidence: 99%
“…Such preference for the oxidative insertiono fP di nto the Ar-halogen bond over the reduction has been recently reported in tandemS uzuki coupling/transfer hydrogenation sequences. [42] It is worth mentioning that in the case of 3-nitroacetophenone, the nitro reduction occurred selectively after 1hwhereas the oxo group reduction occurredo nly in traces ( Table 2, entry 9). However,u pon prolongedr eaction time (2 h) and increaseda mount of HCOONa (6 equiv.…”
Section: Cth Reaction-optimization and Substrate Scopementioning
confidence: 99%
“…Wang et al reported the potential antibacterial and antifungal activity of the Pz 4 ligand [23]. Very recently, Dehury and coworkers reported the synthesis and crystal structure of catalytically active binuclear palladium(II) complexes with Pz 4 and similar ligands [24], but no silver coordination compounds with Pz 4 have been reported An attempt to carry out the reaction in solvothermal conditions at temperatures above 100 °C resulted in degradation of the Pz 4 ligand to smaller fragments (mostly pyrazole). This can be ascribed to the cleavage of C-C and C-N bonds catalyzed by Ag + ions in solution; similar processes have been observed before in other silver(I)-azole ligand systems [25].…”
Section: Introductionmentioning
confidence: 99%
“…Other biphenyl derivatives with industrial applications include polychlorinated biphenyls PCB (C 12 H 10 −xCl x ) organic chlorine compounds widely and used as dielectric fluids and coolant in heat transfer fluids and in carbonless copy paper . In the past decades different strategies for synthesis of biaryls have been extended and the transition metals in their most prominent methods have been used as a catalyst …”
Section: Introductionmentioning
confidence: 99%